Aquisição da linguagem oral e de sinais por um criança ouvinte filha de pais surdos : conhecendo caminhos - Gurjão, Michelle Melo (2013)
Deaf culture has been strengthened by deaf people themselves as well as by their families through meetings in associations, parties, schools for the deaf, games and other common interests, so that this culture can be passed along from generation to generation. Considering such an alliance, it is common for deaf people to marry other deaf people, due to factors associated with identification. This being the case, numerous deaf couples end up having hearing children. Usually, the children of deaf parents grow up as bilingual individuals since they have input from both languages: with their deaf parents, they are exposed to sign language and with their relatives and friends, to Portuguese, due to the interactions that will take place between the child and the deaf and hearing communities. This study aims at analyzing the process of acquisition of Brazilian Sign Language (referred to as Libras in Portuguese) and the Portuguese language in its oral form on the part of a hearing child, who is the daughter of deaf parents. The methodology adopted in the present research is characterized as being qualitative and the method used was the case study. We investigated a hearing daughter of deaf parents between the age of 3 years and 10 months and 4 years and 4 months, through assessments of Portuguese and Libras, as well as through observations during all period and were recorded on a camcorder. The research was carried out both at school and family settings, where we could observe the child's performance in relation to both languages, not to mention other factors that could influence such a process. Data obtained at various stages of assessment and monitoring of the child's daily life have led us to conclude that in this case there were no significant differences regarding the evolution of the two languages. However, it is worth noting that we perceived a greater performance of the child in Libras at the second assessment and at a number of informal moments corresponding to this phase. We understand that the greater exposure to Libras and the permanent corrections of some signs on the part of her father, which does not happen with the Portuguese language, are likely to explain this slight gain. We expect this work to contribute in a way that other reflections may emerge from these considerations on a little investigated topic.